2009
DOI: 10.1182/blood-2008-05-155234
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin-like protein 1 interacts with the GTPase-activating protein Rap1GAP2 and regulates dense granule secretion in platelets

Abstract: The small guanine-nucleotide-binding protein Rap1 plays a key role in platelet aggregation and hemostasis, and we recently identified Rap1GAP2 as the only GTPase-activating protein of Rap1 in platelets. In search of Rap1GAP2-associated proteins, we performed yeast-2-hybrid screening and found synaptotagmin-like protein 1 (Slp1) as a new binding partner. We confirmed the interaction of Rap1GAP2 and Slp1 in transfected COS-1 and HeLa cells and at endogenous level in human platelets. Mapping studies showed that R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…Several other C2-domain-containing proteins have also been detected in platelets ( i.e. , Slp4, DOC2, and synaptotagmin (28, 29, 66)), thus there are potential Ca 2+ sensors which could affect secretion. It is interesting to note that many proteins with 2 C2 domains show distinct roles for each.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other C2-domain-containing proteins have also been detected in platelets ( i.e. , Slp4, DOC2, and synaptotagmin (28, 29, 66)), thus there are potential Ca 2+ sensors which could affect secretion. It is interesting to note that many proteins with 2 C2 domains show distinct roles for each.…”
Section: Discussionmentioning
confidence: 99%
“…phosphatidylserine, PS) (see (27)). Though synaptotagmin-like proteins (Slp1, 4) have been found in platelets (28, 29), a mechanistic understanding of their roles is incomplete. Munc13-4, also contains two C2 domains and appears to play a central role in Ca 2+ -triggered secretion from a number of cells of the hematopoietic lineage (24, 26, 3033).…”
Section: Introductionmentioning
confidence: 99%
“…Using a yeast two-hybrid assay, Smolenski and colleagues showed that SLP1 forms a trimeric complex with Rap1, a ras-like GTPase, and the Rap nucleotide exchange factor RAP1GEF2. SLP1 had a negative effect on dense granule release from permeabilized platelets while RAP1GEF2 addition increased release [75]. The same group showed that SLP4/granuphilin interacts with Rab8 in human platelets and its addition to permeabilized platelets enhanced dense granule release [76].…”
Section: Snare Regulatory Proteinsmentioning
confidence: 99%
“…Sytl1 belongs to the synaptotagmin-like or Slp gene family, which encodes a Rab27-binding protein with a 58-kDa molecular weight (39). In association with Rab27, SYTL1 family proteins facilitate transportation and secretion of cytoplasmic granules, such as platelet granules and zymogen granules, to cellular surfaces and transportation of membrane proteins such as receptor tyrosine kinases (24,25,40).…”
Section: Meis1 Is Required For Hoxa9-induced Leukemogenesis In Vivo Bmentioning
confidence: 99%